Excessive release of endogenous neuropeptide Y into cerebrospinal fluid after treatment of spontaneous subarachnoid haemorrhage and its possible impact on self-reported neuropsychological performance – results of a prospective clinical pilot study on good-grade patients. (2nd December 2018) - Bründl, Elisabeth; Proescholdt, Martin; Schödel, Petra; Bele, Sylvia; Höhne, Julius; Zeman, Florian; Stoerr, Eva-Maria; Brawanski, Alexander; Schebesch, Karl-Michael
ABSTRACT: Objectives : Neuropsychological dysfunction after treatment of spontaneous subarachnoid haemorrhage (sSAH) is common but underreported. The vasoconstrictor neuropeptide Y (NPY) is excessively released after sSAH and in psychiatric disorders. We prospectively analysed the treatment-specific differences in the secretion of endogenous cerebrospinal fluid (CSF) NPY during the acute stage after sSAH and its impact on cognitive processing. Methods : A total of 26 consecutive patients (f:m = 13:8; mean age 50.6 years) with good-grade sSAH were enrolled (drop out n = 5): n = 9 underwent endovascular aneurysm occlusion, n = 6 microsurgery, and n = 6 patients with perimesencephalic SAH received standardized intensive medical care. Ventricular CSF was drawn daily from day 1–10. CSF NPY levels were determined with competitive enzyme immunoassay. All patients underwent neuropsychological self-report assessment [36-Item Short Form Health Survey (SF-36) and ICD-10-Symptom-Rating questionnaire (ISR)] after the onset of sSAH (day 11–35; t1 ) and at the 6-month follow-up (t2 ). Results : At t1, increased mean levels of NPY in CSF significantly correlated with impaired performance in most ISR scores (ISR total p = .018, depression p = .035, anxiety p = .008, nutrition disorder p = .047, supplementary items p = .038) and in several psychological SF-36 items (vitality p = .019, general mental health p = .001, mental component summary p = .025). Discussion : To the best of our knowledge, this study is the first to correlate the levels of endogenous NPY in supratentorial CSF with cognitive outcome in good-grade sSAH patients. Excessive NPY release into CSF may have a short-term influence on the pathogenesis of neuropsychological deficits. The impact of cerebrovascular manipulation on NPY release has to be further elucidated. Abbreviations: ANOVA: analysis of variance; aSAH: aneurysmal subarachnoid haemorrhage; AUC: area under the curve; CBF: cerebral blood flow; CSF: cerebrospinal fluid; CT (scan): computed tomography (scan); CV: cerebral vasospasm; DIND: delayed ischemic neurological deficit; DSA: digital subtraction angiography; EIA: enzyme immunoassay; EV: endovascular aneurysm occlusion; EVD: external ventricular drainage; FU: 6-month follow-up; GCS: Glasgow Coma Scale; Ghp: general health perceptions; GOS: Glasgow Outcome Scale; h: hour/s; HH: Hunt and Hess; ICU: intensive care unit; ISR: ICD-10-Symptom-Rating questionnaire; MCS: mental component summary; Mhi: general mental health; min: minute/s; min-max: minimum – maximum; ml: millilitre; mRS: modified Ranking Scale; MS: microsurgical clipping, microsurgical aneurysm occlusion; ng: nanograms; no. [n]: number; NPY: Neuropeptide Y; p: p value; Pain: bodily pain; PCS: physical component summary; Pfi: physical functioning; pSAH: perimesencephalic subarachnoid haemorrhage; PTSD: posttraumatic stress disorder; QoL: quality of life; Rawhtran: health transition item; Rolem: role limitations because of emotional problems; Rolph: role limitations due to physical health problems; SAH: subarachnoid haemorrhage; SD: standard deviation; SF-36: 36-Item Short Form Health Survey; Social: social functioning; sSAH: spontaneous subarachnoid haemorrhage; TCD: trans-cranial Doppler ultrasound; (test) t1 : test in the sub-acute phase after the onset of bleeding (between day 11 and 35 after subarachnoid haemorrhage); (test) t2 : test in the short-term (chronic phase) after treatment at 6-month follow-up; test t1 - t2 : intergroup development from t1 to t2 ; Vital: vitality; vs: versus.